PENGARUH PROFITABILITAS DAN INTENSITAS MODAL TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BEI PADA TAHUN 2018-2021 - Elma Rebecca Tania Simanjuntak; Lorina Siregar Sudjiman (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2022)
The phenomenon of the issuer of a new coal mining company, PT Bukit Asam Tbk, recorded a decline in performance, even though world coal prices were on an upward trend. This caused PTBA's shares to drop 22% to Rp. 3.99 compared to last year's Rp. 5.12 trillion. In addition, the cost of revenue also fell to Rp. 2.97 trillion last year amounting to Rp. 3.59 trillion. This study wants to determine the effect of profitability and capital intensity on tax aggressiveness in coal mining companies listed on the Indonesia Stock Exchange in 2018-2021. The research method uses a quantitative approach using secondary data. The research population is all coal mining companies listed on the IDX in 2018-2021, using purposive sampling technique, data analysis using multiple linear regression analysis with the IBM SPSS program analysis tool version 22. The results show that partially profitability has a significant effect on tax aggressiveness, intensity capital has a significant effect on tax aggressiveness, while simultaneously profitability and capital intensity have a significant effect on tax aggressiveness in 24 coal mining companies listed on the IDX in 2018-2020.